REKRUTMEN BAKAL CALON WALIKOTA DAN WAKIL WALIKOTA KOALISI PARTAI DEMOKRAT, GERINDRA, DAN PKS PADA PILKADA KOTA PEKANBARU TAHUN 2017 - Chanie Prastanya; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The research is based on regional election in Pekanbaru City 2017 to choosed Mayor and Vice Mayor. Regional election was held on 15 February 2017. Candidates for Mayor and Vice Mayor is Syahril-Said Zohrin, Herman Nazar-Defiwwarman, Firdaus-Ayat Cahyadi and Dastrayani Bibra-Said Usman. The Mayor and Vice Mayor is elected incumbent candidates Firdaus and Ayat Cahyadi from coalition Demokrat party, Gerindra and PKS.The purpose of this result is to know recruitment mechanism from Demokrat Party, Gerindra and PKS to choose the candidates and to know factor the coalition. Method used in this research is descriptive methods with qualitative type. Types of data on this researchis primary and secondary data. The data collected in this research is documentation and interview. The technical data analysis used is descriptive qualitative data analysisThe result is Demokrat Party, Gerindra and PKS have their own recruitment mechanism. Democrat Party and Gerindra would selected and test the candidates and PKS would voted the candidates in publicly internal. Those who are selected candidates of Demokrat Party, Gerindra and PKS are chosen by the board of the leadership center party in Jakarta. Factor of the coalition is the same vision and mission, the figur of the candidates, sustainability of the progamme and other.Keywords: Recruitment, Political Party, Regional Election, Coalition